1995
DOI: 10.1111/j.1600-0609.1995.tb00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility of microcytic red blood cells to in vitro oxidative stress

Abstract: Oxidative damage to erythrocytes in thalassaemia has been related to generation of free radicals by an excess of denaturated α‐ or β‐globin chains, intracellular iron overload and low concentration of normal haemoglobin (HGB). Two good indicators of such oxidative damage are the high red blood cell (RBC) malonyldialdehyde (MDA) production detected following exogenous oxidant stress and the decrease of pyrimidine 5′‐nucleotidase (P5N), the most sensitive enzyme to SH‐group damage in vivo. Conflicting data, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
2
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 29 publications
6
40
2
5
Order By: Relevance
“…A study investigated oxidative status in thalassemia major subjects, where a significantly increased oxidative stress compared to other forms of microcytic anemias including d thalassemia major and iron deficiency anemia was detected (44). In respect of increased TOS and OSI, our findings were consistent with that study (44).…”
Section: Discussionsupporting
confidence: 92%
“…A study investigated oxidative status in thalassemia major subjects, where a significantly increased oxidative stress compared to other forms of microcytic anemias including d thalassemia major and iron deficiency anemia was detected (44). In respect of increased TOS and OSI, our findings were consistent with that study (44).…”
Section: Discussionsupporting
confidence: 92%
“…In the literature (9,14,19), microcytic red blood cells had higher susceptibility to oxidant and high malonyldialdehyde production. Similarly, our results indicated that blood ROS concentrations were higher in patients with IDA than controls.…”
Section: Discussionmentioning
confidence: 98%
“…Free radical action and lipid peroxidation have been suggested as potentially important causative agents of aging and several types of human diseases [24]. Reactive oxygen species (ROS) have been implicated in damage to erythrocytes in patients with β-thalassemia, sickle cell anemia, glucose-6-phosphate dehydrogenase deficiency and other hemoglobinopathies [25,26]. Aqueous extracts of Conyza canadensis interact in some way with the biological membranes.…”
Section: Resultsmentioning
confidence: 99%